Digitizing and Disclosing Personal Data: The Proliferation of State Criminal Records on the Internet. Issue 3 (29th August 2021) - Lageson, Sarah E.; Webster, Elizabeth; Sandoval, Juan R.
Abstract : Digitization and the release of public records on the Internet have expanded the reach and uses of criminal record data in the United States. This study analyzes the types and volume of personally identifiable data released on the Internet via two hundred public governmental websites for law enforcement, criminal courts, corrections, and criminal record repositories in each state. We find that public disclosures often include information valuable to the personal data economy, including the full name, birthdate, home address, and physical characteristics of arrestees, detainees, and defendants. Using administrative data, we also estimate the volume of data disclosed online. Our findings highlight the mass dissemination of pre-conviction data: every year, over ten million arrests, 4.5 million mug shots, and 14.7 million criminal court proceedings are digitally released at no cost. Post-conviction, approximately 6.5 million current and former prisoners and 12.5 million people with a felony conviction have a record on the Internet. While justified through public records laws, such broad disclosures reveal an imbalance between the "transparency" of data releases that facilitate monitoring of state action and those that facilitate monitoring individual people. The results show how the criminal legal system increasingly distributes Internet privacy violations and community surveillance as part of contemporary punishment.